2020
DOI: 10.1007/s40744-020-00229-0
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Comorbidities on Disease Activity, Patient Global Assessment, and Function in Psoriatic Arthritis: A Cross-Sectional Study

Abstract: Introduction The aim of this study was to evaluate the impact of comorbidities on disease activity, patient’s impact of the disease, patient global assessment, and function in psoriatic arthritis (PsA). Methods Consecutive PsA patients were enrolled in this cross-sectional study. During the visit, the patients underwent a complete physical examination and clinical/laboratory data were collected, including type and number of comorbidities, recorded as simple comorbidity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A recent study also showed that high prevalence of metabolic syndrome in PsA was associated with the severity of PsA [27]. Also, Ennio Lubrano et al found that anxiety (b = 14.46, p \ 0.001) and fibromyalgia (b = 6.46, p = 0.025) was also positively correlated to DAPSA [28]. The association of comorbidities with disease activity warrants a prospective longitudinal study to confirm their casual relationships.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…A recent study also showed that high prevalence of metabolic syndrome in PsA was associated with the severity of PsA [27]. Also, Ennio Lubrano et al found that anxiety (b = 14.46, p \ 0.001) and fibromyalgia (b = 6.46, p = 0.025) was also positively correlated to DAPSA [28]. The association of comorbidities with disease activity warrants a prospective longitudinal study to confirm their casual relationships.…”
Section: Discussionmentioning
confidence: 92%
“…On the other hand, PsA patients with hypertension or cardiovascular disease are more unlikely to achieve remission/LDA [ 29 ]. Several studies have shown the increased risk of cardiovascular disease in PsA patients [ 30 , 31 ]. Therefore, we highly recommend screening for comorbidities in PsA patients, especially those with more active disease.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, the leptin level, obesity, and depression predicted persistent clinical PsA activity. Recently, Lubrano et al [29] demonstrated that the number of comorbidities, including general comorbidities, anxiety and bromyalgia in particular, had an impact on the DAPSA scores. Other comorbidities, such as depression, diabetes and obesity, did not in uence activity [29].…”
Section: Discussionmentioning
confidence: 99%
“…Inflammatory activity in one or more disease domains may persist due to multidrug resistance, clinical or immunologic mechanisms (including anti-drug antibodies), or other factors such as non-adherence. On the other hand, factors such as comorbidity and in particular fibromyalgia, anxiety, and depression may play a role, making a patient resistant to multiple treatment strategies [ 10 12 ]. In RA, a recent international survey showed the need for a more holistic approach for the D2T patient [ 13 ].…”
Section: Introductionmentioning
confidence: 99%